Benthic Macroinvertebrate Community as an Indicator of Stream Health: The Effects of Land Use on Stream Benthic Macroinvertebrates - Deborde, Danielle Dominique D.; Hernandez, Maria Brenda M.; Magbanua, Francis S. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 28 No 2 (2016), 2016)
Biomonitoring of stream health in the tropics still emphasize on the use of standard water chemistry methods (physicochemical variables), which require expensive and elaborate measuring apparatus. In this study, the reliability of benthic macroinvertebrates as bioindicators of freshwater streams was carried out. The study also attempted to determine the discriminating power of various biotic indices in characterizing sites across land use. Benthic macroinvertebrate samples were obtained from nine streams in Silago, Southern Leyte and were identified to family level. One-way analysis of variance was performed on various biotic indices to assess the water quality of streams based on land use. Average Tolerance Score per Taxon (ATSPT) was the only biotic index that differentiated the nine streams based on land use (P<0.001). Forested sites achieved the lowest ATSPT score, whereas mixed forested-agricultural sites had the highest ATSPT scores. Physicochemical variables (e.g., stream width, conductivity, total dissolved solids, water temperature) and biological metrics (e.g., Simpson’s diversity index, total macroinvertebrate density) used in the study supported this assessment. The results show that benthic macroinvertebrates can be used as potential biomonitoring tool to evaluate the ecological integrity of waterways in the country. Long-term data sets will be generated from future sampling efforts for the development of the Philippine Biotic Index. Keywords: Average Tolerance Score per Taxon (ATSPT), biotic indices, stream monitoring, physicochemical, Philippines